In Yarrowia lipolytica erythritol catabolism ends with erythrose phosphate. (10th December 2019) - Niang, Papa Makhona; Arguelles‐Arias, Anthony; Steels, Sebastien; Denies, Olivia; Nicaud, Jean‐Marc; Fickers, Patrick
Abstract: In response to osmotic stress, the yeast Yarrowia lipolytica produces erythritol, a four‐carbon sugar alcohol, from erythrose‐P, an intermediate of the pentose phosphate pathway. Under non‐stressing conditions (isotonic environment), the produced erythritol is subsequently recycled into erythrose‐P that can feed the pentose phosphate pathway. Herein, gene YALI0F01584g was characterized as involved in the erythritol catabolic pathway. Several experimental evidences suggested that it encodes an erythrulose‐1P isomerase that converts erythrulose‐1P into erythrulose‐4P. On the basis of our previous reports and results gathered in this study with genetically modified strains, including ΔYALI0F01584g and ΔYALI0F01628g disrupted mutants, the entire erythritol catabolic pathway has been characterized.